Republic of Fiji : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Fiji. (IMF Staff Country Reports; Country Report, 2016)
Fiji is enjoying a strong growth momentum due to accommodative policies, robust tourism and strong remittances, and an improvement in the terms of trade. The smooth and peaceful elections in September 2014 marked the return to democracy-leading to a normalization in relations with development partners, further boosting investor and consumer confidence. While addressing infrastructure gaps and further improving the business climate will be critical to ensure strong, sustainable and more inclusive growth, this must be balanced against the need to consolidate fiscal policy. Risks are tilted to the downside, related to external developments and prolonged accommodative policy settings.